ANALYSIS OF GREEN ECONOMY APPLICATIONS IN INDONESIA IN THE PERSPECTIVE OF SHARIA MAQASHID - Rusli Siri (Sean Institute, 2023)
This research was motivated by business expansion activities carried out by good companies in Indonesia. However, unfortunately, when the company continues to build but does not pay attention to the sustainability aspect of the business. The future of the business is increasingly bleak. Therefore, the concept of expansion is needed accompanied by a green economy based on sharia maqashid. This study aims to analyze the application of Green Economy in Indonesia from the perspective of maqashid syariah. This research is a qualitative research using a phenomenon approach in the form of library research. Where researchers experience events then explain in descriptive form related to the concept of Green Economy and the relevance of its implementation in the Indonesian context and how it is applied in the perspective of safeguarding religion, soul, reason, offspring, property, and the environment. The results show that in designing an implementative, reliable and comprehensive green economy implementation model, Indonesia should have a truly green economic model and relevant to the characteristics of the Indonesian nation based on sharia maqashid that is in harmony with the sociocultural of Indonesian society. The principle of low carbon is basically in line with the maintenance of soul and reason. The principle of resource efficient is also in line with the maintenance of offspring and property. Likewise, the principle of socially inclussive is found in the five aspects of maintenance in the concept of maqashid sharia. Based on the analysis, researchers concluded that in general the application of the green economy concept in Indonesia still needs to be revised. There are still many obstacles faced in the field. Among them, the company is more concerned with profits, without paying attention to business sustainability. Therefore, in developing a business, a maqashid sharia approach is needed so that the business carried out is blessed both in the world and at the end. As recommended by Islam, namely the balance of the world and the hereafter. For this reason, it is expected that companies that expand their business pay attention to the principles of green economy based on sharia maqashid.